Magnesium sulphate reversal of established bupivacaine electrophysiological cardiotoxicity - Reed, Anthony Raddon (Department of Anaesthesia, 2018)
The results of this study show that in intact rats magnesium produces a more rapid resolution of bupivacaine induced electrophysiological changes than placebo. The improvements are in rhythm and electrical conduction, although this is often at the expense of potentiating the bradycardic effects of bupivacaine toxicity. Whilst the bradycardia remains a problem it is potentially more amenable to therapy than the changes in rhythm and conduction which magnesium sulphate reversed. The opportunity therefore exists to explore the possibility of combining magnesium with a positive chronotrophic agent such as dobutamine.